Comparative Analysis of The Laws of Ṭahārah Between Chatsonic Artificial Intelligence and The Classical Islamic Text Fatḥ Al-Qarīb - Qoyyimah, Maysarotud Dinul; Sulaikho, Siti (Faculty of Tarbiyah, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2024)
Chatsonic is an advanced Artificial Intelligence technology that has been widely utilized by students and educators to facilitate learning processes. This study aims to evaluate the accuracy of Chatsonic in interpreting the concept of Ṭahārah based on the text Fatḥ al-Qarīb, analysing its strengths and weaknesses. This research employs a qualitative method with a descriptive approach. Data were collected from documents and analysed using the qualitative content analysis procedure developed by Philipp Mayring. The results show that while Chatsonic can explain certain aspects of Ṭahārah, there are several inaccuracies in its interpretation. For example, Chatsonic defines muṭlaq water as